PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NOMOR 105 TENTANG PEMBIAYAAN MUDHARABAH PADA BAITUL MAAL WAT TAMWIL (STUDI EMPIRIS PADA KOPERASI SYARIAH DI ACEH BESAR) - Adelina, Liza; Suazhari, Suazhari (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study is a descriptive study about the implementation of the Statement of Financial Accounting Standard (SFAS) 105 mudharabah financing at Sharia Cooperatives in Aceh Besar. The aim of this study was to find out how the implementation of SFAS 105 in term of recognition, measurement, presentation, and disclosure in mudharabah financing transactions at Sharia Cooveratives in Aceh Besar. The population of this study is Sharia Cooperative in Aceh Besar. Samples taken were 5 of 21 Sharia Cooperatives, which were taken using purposive sampling method. The analisys is done by comparing the implementation of accounting treatment in mudharabah financing transactions with SFAS 105. The results showed that the accounting treatment of Sharia Cooperatives in Aceh Besar in term of recognition, measurement, and disclosure was non fully in accordance with SFAS 105, while the accounting treatment on the presentation side was in accordance with SFAS 105.